Pengaruh Promosi Dan Lokasi Terhadap Keputusan Pembelian Konsumen Keripik Cabe Ibu Jumi Di Kelurahan Pangkalan Sesai Kota Dumai - Ardi Syahputra (Tamaddun Ummah (JTU), 2022)
The purchase decision is an important factor that must be considered by the company. The purchase decision is the final stage in determining or knowing a product and deciding to buy the desired product. Purchase decisions can be influenced by several factors, namely product, place, price and promotion. Location is also one of the important factors to determine the purchase decision. Location is synonymous with where a company has to stay and carry out its activities. Location is one of the important factors that will affect the development of a business.This study uses a quantitative method approach, the data used are primary data obtained through distributing questionnaires to 371 respondents. The data analysis uses multiple regression analysis with the help of SPPS 24.0 windows software.The results showed that the influence of promotion and location on purchasing decisions together gave a positive and significant influence on purchasing decisions with a contribution of 18.5%. Partially. promotions make a positive and significant contribution to purchasing decisions